Find Out East Sakerta Tourism Village Thematic Concept for Sign System Design - Santi Maudiarti; Hanni Adriani (Jurnal Pembelajaran Inovatif, 2021)
The tourism industry is one of the primary needs for the life of modern society today. Because of these factors, it makes the need for recreation or tourism increases. East Sakerta Tourism Village is one of the leading tourist destinations in the Kuningan Regency. However, the leading Tourism Village of East Sakerta has the disadvantage of not having a thematic sign system that can provide a brand image and facilitate tourists who will visit the area. This study has the following objectives to find out a thematic concept for sign system at the East Sakerta Tourism Village. The research method used is a qualitative method. This data collection method is carried out using the Focus Group Discussion (FGD) method. Primary data collection was carried out directly and purposive sampling by interviewing key people, namely the village government apparatus, tourism community leaders (kompepar), and the community. FGD method used to find out about the history, legends, and uniqueness of the East Sakerta Village to support the realization of thematic sign system design. The results of the FGD research show that the agreed thematic concept is "Tumaritis" which is a village in the Sundanese and Javanese puppet which has a philosophy of mutual protection, security, and prosperity